2004
DOI: 10.1093/carcin/bgh303
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nucleotide excision repair and GSTM1-null genotypes influence anti-B[a]PDE-DNA adduct levels in mononuclear white blood cells of highly PAH-exposed coke oven workers

Abstract: It is important to identify the potential genetic-susceptible factors that are able to modulate individual responses to exposure to carcinogenic polycyclic aromatic hydrocarbons (PAHs). In the present study we evaluated the influence of four polymorphisms of nucleotide excision repair (NER) genes [xeroderma pigmentosum-C (XPC)-PAT +/-, xeroderma pigmentosum-A (XPA) 5' non-coding region-A23G, XPD-exon 23 A35931C Lys751Gln, xeroderma pigmentosum-D (XPD)-exon 10 G23591A Asp312Asn] and that of glutathione S-transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 40 publications
4
60
1
1
Order By: Relevance
“…Both biological and biochemical evidence also indicate the importance of XPC Lys939Gln polymorphism associated with a differential repair capacity. 63 -66 Low repair capacity of benzo(a)pyrene DNA adducts was also observed in lymphocytes of individuals with this XPC variant, 67 although the protein levels of XPC were not measured in that study. Moreover, XPC has two other polymorphisms in linkage with the Gln allele -an insertion of an 83-bp ATs (PAT) in intron 9 and an exchange of C to A in splicing site of intron 11 -that might contribute to a decreased expression of XPC, due to abnormalities in RNA stability and splicing process.…”
Section: Discussionmentioning
confidence: 85%
“…Both biological and biochemical evidence also indicate the importance of XPC Lys939Gln polymorphism associated with a differential repair capacity. 63 -66 Low repair capacity of benzo(a)pyrene DNA adducts was also observed in lymphocytes of individuals with this XPC variant, 67 although the protein levels of XPC were not measured in that study. Moreover, XPC has two other polymorphisms in linkage with the Gln allele -an insertion of an 83-bp ATs (PAT) in intron 9 and an exchange of C to A in splicing site of intron 11 -that might contribute to a decreased expression of XPC, due to abnormalities in RNA stability and splicing process.…”
Section: Discussionmentioning
confidence: 85%
“…Qiao et al [33] studied XPC genotype-related DRC using a host-cell reactivation assay and found that healthy subjects with the homozygous variant genotype of the PAT polymorphism (+/+) exhibited lower DRC as compared to wild-type carriers (-/-). In another study, the PAT +/+ genotype was associated with higher levels of anti-BPDE-DNA adducts than those with the -/-genotype in coke oven workers [36].…”
Section: Discussionmentioning
confidence: 91%
“…25,30 At the Institute of Occupational Medicine and Environmental Health in Sosnowiec: (i) PBL cultures for MN detection were prepared and MN analyses performed; (ii) PBLs for adduct analyses were isolated in Ficoll separating solution (Seromed, Berlin, Germany) within 4 hr after blood collection and kept frozen at 280°C, until they were sent to the Department of Environmental Medicine and Public Health in Padova (Italy), where DNA was extracted. Data on other possible elevated nonoccupational PAH exposure (diet, environment) and consumption of fruit and vegetables were collected by means of a questionnaire, as previously described 23,24 (i.e., high dietary intake of PAHs was the consumption of charcoaled meat (PAH-rich meals) more than once a week; indoor and environmental exposure to PAHs was the use of wood or coal to heat the home, and an index of location of residence that included intense local traffic and presence of industries in the residential area). This study was reviewed by the appropriate Ethics Committee of the Institute of Occupational Medicine and Environmental Health in Sosnowiec.…”
Section: Methodsmentioning
confidence: 99%
“…[20][21][22] Finally, increased anti-B[a]PDE-DNA and MN levels have been related to occupational (cokeries) and environmental (smoking, diet) PAH exposure. [23][24][25][26] However, no studies have addressed whether PAH exposure alters epigenetic patterns in PBLs from occupationally exposed people, who are, therefore, at high risk of lung carcinogenesis.…”
mentioning
confidence: 99%